Clinical remission of rheumatoid arthritis in a multicenter real-world study in Asia-Pacific region - Xing Sun; Ru Li; Yueming Cai; Adeeba Al-Herz; Manjari Lahiri; Minhaj Rahim Choudhury; Rudy Hidayat; Bagus Putu Putra Suryana; Yuko Kaneko; Keishi Fujio; Nguyen Van Hung; Sapan Pandya; et al. (Elsevier, 2021)
Background: Clinical remission is an attainable goal for Rheumatoid Arthritis (RA). However, data on RA remission rates from multinational studies in the Asia-Pacific region are limited. We conducted a cross-sectional multicentric study to evaluate the clinical remission status and the related factors in RA patients in the Asia-Pacific region. Methods: RA patients receiving standard care were enrolled consecutively from 17 sites in 11 countries from APLAR RA SIG group. Data were collected on-site by rheumatologists with a standardized case-report form. Remission was analyzed by different definitions including disease activity score using 28 joints (DAS28) based on ESR and CRP, clinical disease activity index (CDAI), simplified disease activity index (SDAI), Boolean remission definition, and clinical deep remission (CliDR). Logistic regression was used to determine related factors of remission. Findings: A total of 2010 RA patients was included in the study, the overall remission rates were 62•3% (DAS28-CRP), 35•5% (DAS28-ESR), 30•8% (CDAI), 26•5% (SDAI), 24•7% (Boolean), and 17•1% (CliDR), respectively, and varied from countries to countries in the Asia-Pacific region. Biological and targeted synthetic disease-modifying antirheumatic drugs (b/tsDMARDs) prescription rate was low (17•9%). Compared to patients in non-remission, patients in remission had higher rates of b/tsDMARDs usage and lower rates of GC usage. The favorable related factors were male sex, younger age, fewer comorbidities, fewer extra-articular manifestations (EAM), and use of b/tsDMARDs, while treatment with GC was negatively related to remission. Interpretation: Remission rates were low and varied in the Asia-Pacific region. Treatment with b/tsDMARDs and less GC usage were related to higher remission rate. There is an unmet need for RA remission in the Asia-Pacific region.